The Politics of States and Local Governments Creation in Nigeria: An Appraisal - Adeyemi, O. Oluwatobi (European Journal of Sustainable Development, 2013)
State and local governments are instruments of development aimed at bringinggovernment closer to the people so as to ensure their greater and equitable participation inthe process of governance. However, in Nigeria, the pattern of infrastructuraldevelopment is concentrated in the state and local government headquarters, rather thanadopting holistic developmental process, which has engender stiff competition andscramble for local government creation among various groups in the polity..Against this background, this paper examines the process of state and local governmentcreation in Nigeria from 1960 till date. The study found that state and local governmenthave and become an avenue for obtaining more allocations from the federal governmentcoffer, as well as political representations at the national assembly.The study presumably hopes to provide useful solution to frequent agitation for creationof more state and local government by recommending that government at all levels(federal, state and local) should be responsive to the aspirations of the people at grassrootso as to reduce further agitation and ensure political stability and development. Themethodology employed is qualitative method collections of data.